PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF PROFESSIONAL SELF-DETERMINATION OF TEENAGERS INCLINED TO DEVIANT BEHAVIOR - Galina N. Zhulina (Russian State Vocational Pedagogical University, 2016)
The aim of the research is to study the peculiarities of teenagers' professional self-determination inclined to deviant behavior, the design of the psychological and pedagogical program of professional self-determination for adolescents. Methods. The methods involve theoretical analysis on the research problem, empirical methods and techniques (methods in diagnostics of tendency to deviant behavior (SOPS) by A. N. Orel, questionnaire to determine the professional readiness by L. N. Kabardova; questionnaire «The knowledge about the world of professions» by E. A. Klimov; the questionnaire for determining personal professional perspective by N. S. Pryazhnikov), methods of mathematical statistics (the MannWhitney test). Results. The age differences of some components of adolescents' professional self-determination are revealed. It is proved that there are differences for some components of professional self-determination of adolescents, inclined and not inclined to deviant behavior. The program project of psychological and pedagogical support of professional self-determination for adolescents is proposed. Scientific novelty and theoretical significance of the work consists in the expansion of scientific ideas about the psychological characteristics of adolescents who are prone to deviant forms of behavior. The study clarifies the scientific view of professional self-determination of a teenager and organization of psychological and pedagogical support of driving in instability of society. Practical significance. The results allow to solve practical problems of professional self-determination of adolescents. The obtained results can be used in advisory, developmental directions of practical psychologist in education, in building programs of prevention deviant behavior for teenagers. The results of the study served as the basis for designing the program of psycho-pedagogical support of adolescents' professional self-determination.